Nursing Care at by. Z and By. I Thrush Performed Oral Hygiene Measures in the Ade Irma Suryani Room of Arjawinangun Hospital - Putri, Salsabila Eka; Zaitun, Zaitun; Yuliani, Ayu (Ann Publisher, 2025)
Background: Babies at a young age are susceptible to diseases. Immunity that has not yet formed makes it easier for babies to be infected with bacteria or fungi. Oral thrush is one of the most common infections. According to research conducted by Eranika in 2016, in Indonesia, around 2.4 million babies have oral thrush. There are many ways to deal with oral thrush; one is to maintain oral health through oral hygiene. Consistent oral hygiene measures in babies can reduce the risk of oral thrush, preventing serious problems. Purpose: To moisturize the oral mucosa and reduce plaque in the mouth. Method: Using qualitative methods with a case study approach. The subjects used in this case study were two infants with oral thrush. Data collection techniques use interviews, observation, and documentation. Results: An assessment was conducted on infants with the same complaints. Both have a nursing diagnosis of oral mucosal membrane disorders. The intervention consisted of oral hygiene measures. After 5 days of implementation, there were significant changes in both subjects: appetite improved, drinking improved, they were not fussy, had a moist oral mucosa, reduced white plaques, and were clean. Conclusion: Oral hygiene is effective in overcoming oral thrush in babies' mouths.